IMPROVING READING COMPREHENSION SKILLS BY USING THE COOPERATIVE LEARNING MODEL - ., Yuliana (ENGLISH JOURNAL, 2020)
This research aims to find out the use of Cooperative Learning model in improving reading ability (Reading Comprehension Skills). This action research was undertaken over a period of three months from the beginning of January 2020 to the end of March 2020 which involved 30 students consisting of 17 male students and 13 female students. Cooperative Learning Model by using the Cutting Passage method was successfully demonstrated by increasing the value of student evaluation results. This method makes students become disciplined in searching for vocabulary before starting learning to understand reading. This method leaves the teacher's habit in delivering material not only using lecture and discussion methods.